Brain mechanisms of abnormal temperature perception in cold allodynia induced by ciguatoxin. Issue 1 (January 2017) - Eisenblätter, Anneka; Lewis, Richard; Dörfler, Arnd; Forster, Clemens; Zimmermann, Katharina
Abstract : Objective: Cold allodynia occurs as a major symptom of neuropathic pain states. It remains poorly treated with current analgesics. Ciguatoxins (CTXs), ichthyosarcotoxins that cause ciguatera, produce a large peripheral sensitization to dynamic cold stimuli in Aδ‐fibers by activating sodium channels without producing heat or mechanical allodynia. We used CTXs as a surrogate model of cold allodynia to dissect the framework of cold allodynia–activated central pain pathways. Methods: Reversible cold allodynia was induced in healthy male volunteers by shallow intracutaneous injection of low millimolar concentrations of CTX into the dorsal skin of the forefoot. Cold and warm stimuli were delivered to the treated and the control site using a Peltier‐driven thermotest device. Functional magnetic resonance imaging (fMRI) scans were acquired with a 3T MRI scanner using a blood oxygen level–dependent (BOLD) protocol. Results: The CTX‐induced substantial peripheral sensitization to cooling stimuli in Aδ‐fibers is particularly retrieved in BOLD changes due to dynamic temperature changes and less during constant cooling. Brain areas that responded during cold allodynia were almost always located bilaterally and appeared in the medial insula, medial cingulate cortex, secondary somatosensory cortex, frontal areas, and cerebellum. Whereas these areas also produced changes in BOLD signal during the dynamic warming stimulus on the control site, they remained silent during the warming stimuli on the injected site. Interpretation: We describe the defining feature of the cold allodynia pain percept in the human brain and illustrate why ciguatera sufferers often report a perceptual temperature reversal. ANN NEUROL 2017;81:104–116